The Politics of Place. - Lunström, Jan-Erik; Sjöström, Johan; Ponte, Alessandra; Sörlin, Sverker; Taylor, John; BildMuseet, Umea; Eldsvik Konst och Kultur, Sollentuna; The Finnish Museum of Photography, Helsinki; Länsmuseet Västernorrland, Härnörsand (Umea : BildMuseet, 2002)
Gursky, Andreas ; H, Nanna ; Haughey, Anthony ; Klingberg, Margareta ; Lantz, Maria ; Niedermayr, Walter ; Pollard, Ingrid ; Puranen, Jorma ; Rodland, Torbjorn ; Sekula, allan ; Wall, Jeff
BildMuseet, Umea, Feb-April 2002 / Eldsvik Konst och Kultur, Sollentuna, Aug-Oct 2002 / The Finnish Museum of Photography, Helsinki, Jan-March 2003 / Länsmuseet Västernorrland, Härnösand, March-May 2003
kunstcatalogus